Dynamic Response and Failure Characteristics of Slope with Weak Interlayer under Action of Near-Fault Ground Motion - Bing Yang; Jiangrong Hou; Yifei Liu; Zihong Zhou (Shock and Vibration)
Investigations into the Wenchuan earthquake (2008, China) demonstrated that landslides were concentrated in the near-fault areas, and numerous large-scale landslides occurred in slopes with weak interlayers. A mathematical model was established based on the shear beam theory, while a numerical model was developed based on the discrete element method which perfectly matched layer boundary theory. Through a theoretical analysis and numerical simulation, the dynamic response and failure modes of the slope with a weak interlayer under the near-fault ground motion were studied. It was found that a combined effect took place between the near-fault ground motion and the weak interlayer, causing the slope near a fault to be destroyed more easily. The coupling between the near-fault ground motion and the weak interlayer leads to a maximum amplification effect of the slope. The existence of a weak interlayer induces nonconforming vibration between the upper and the lower rock masses of the interlayer. The variation in the amplification effect along the slope elevation is related to the ratio of the input seismic period to the natural slope period. Under horizontal ground motion, weak interlayers will be subjected to impacting and shearing action. The failure mode of the slope with a weak interlayer under near-fault ground motion can be expressed as a trailing edge tension crack, as well as weak interlayer impacting and shearing failure.